2020
DOI: 10.1101/2020.04.21.053611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining Epidermal Stem Cell Fate Infidelity and Immunogenicity in Hidradenitis Suppurativa at the Single-Cell Resolution

Abstract: words)Hidradenitis suppurativa (HS) is a severe chronic inflammatory skin disease affecting human apocrine sweat gland-bearing skin regions. One unique feature of HS is the development of keratinized sinus tracts that grow extensively deep in the dermis and are highly immunogenic. Here, we demonstrated that the stem cell fate infidelity exists in the HS sinus tracts, which exhibit features of both surface epidermis and appendages. Using single cell transcriptome analyses, we finely dissected different compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Dunstan et al also identified KRT15, 19 and nestin positive cells in the tendrils thus showing that ORS cells are capable of an uncontrolled proliferation and invasiveness becoming corneocytes (KRT10+) or going back to the multipotency. This finding was corroborated by scRNAseq performed earlier by Marohn et al 44 The results from the scRNA-seq analysis revealed that cells forming tendrils shared common transcripts with the cells of infundibulum/sweat duct, therefore expressing high levels of genes specific for sweat and sebaceous glands, albeit their morphology and differentiation program resembled interfollicular keratinocytes.…”
Section: Skin Histology and Integrated Omics Data Validationsupporting
confidence: 80%
See 1 more Smart Citation
“…Dunstan et al also identified KRT15, 19 and nestin positive cells in the tendrils thus showing that ORS cells are capable of an uncontrolled proliferation and invasiveness becoming corneocytes (KRT10+) or going back to the multipotency. This finding was corroborated by scRNAseq performed earlier by Marohn et al 44 The results from the scRNA-seq analysis revealed that cells forming tendrils shared common transcripts with the cells of infundibulum/sweat duct, therefore expressing high levels of genes specific for sweat and sebaceous glands, albeit their morphology and differentiation program resembled interfollicular keratinocytes.…”
Section: Skin Histology and Integrated Omics Data Validationsupporting
confidence: 80%
“…Loss of hair follicle stem cells identity is a peculiar characteristic of HS, and it seems to be independent to the disease's varied inflammatory response that may be initiated by chemokines and cytokines expressed by cells in the tendrils and fueled by keratin spilled from the final cysts 43,44 .…”
Section: Skin Histology and Integrated Omics Data Validationmentioning
confidence: 99%